Combined AHP-TOPSIS-IPA and Statistical Analyses for Implications to One Belt One Road Initiatives - Zhao , Shulan (International Journal of Multidisciplinary in Management and Tourism, 2021)
Based on a concerted multilateralism principle of one-belt-one-road (OBOR) initiatives, this study proposes and demonstrates that the OBOR initiative should support the PEST (political, economic, social, and technology) environments and the competitive-advantage goals of OBOR’s participating countries. Besides, the competitive-advantage goals that OBOR investments can support are generally the ultimate incentives for the participating countries. The data provides evidential supports. In addition, this study employs AHP, TOPSIS, and IPA (Importance-Performance Analysis) to understand the nature and level of perceived success in ASEAN’s one-belt-one-road (OBOR) initiatives. For the primary-data collection, this study focuses predominantly on the PEST environments. Overall, the study uses a risk management model to link microeconomic to macroeconomic environments, leading to the 4C model for OBOR initiatives and implementation. AHP and TOPSIS prioritize importance, and importance-performance analysis (IPA) captures the performance gaps to draw implications for the policymakers for OBOR’s (one belt one road) participating countries.